2012
DOI: 10.1371/journal.pone.0051820
|View full text |Cite
|
Sign up to set email alerts
|

Hexachlorophene Is a Potent KCNQ1/KCNE1 Potassium Channel Activator Which Rescues LQTs Mutants

Abstract: The voltage-gated KCNQ1 potassium channel is expressed in cardiac tissues, and coassembly of KCNQ1 with an auxiliary KCNE1 subunit mediates a slowly activating current that accelerates the repolarization of action potential in cardiomyocytes. Mutations of KCNQ1 genes that result in reduction or loss of channel activity cause prolongation of repolarization during action potential, thereby causing long QT syndrome (LQTs). Small molecule activators of KCNQ1/KCNE1 are useful both for understanding the mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
(48 reference statements)
0
25
1
1
Order By: Relevance
“…However, there are reports, for example, suggesting that KCNEs affect other Kv channels, including Kv4.2 (41). It would also be interesting to determine whether the specificity for unsaturated KCNQ1/KCNE stoichiometry is in fact applicable to or different from that by other allosteric modulators (42,43), including ones discovered recently (12,44). The continuum of incremental subunit coassembly and that of differential pharmacological sensitivity to small-molecule modulators highlight both complexity of the regulation and opportunities to develop therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are reports, for example, suggesting that KCNEs affect other Kv channels, including Kv4.2 (41). It would also be interesting to determine whether the specificity for unsaturated KCNQ1/KCNE stoichiometry is in fact applicable to or different from that by other allosteric modulators (42,43), including ones discovered recently (12,44). The continuum of incremental subunit coassembly and that of differential pharmacological sensitivity to small-molecule modulators highlight both complexity of the regulation and opportunities to develop therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A combined approach of electrophysiology and molecular dynamic simulation indicated that ML277 binds to the side pockets between adjacent KCNQ1 subunits to allosterically modify channel gating 94 . Nonspecific compounds such as the chloride channel blockers mefenamic acid and DIDS, and the anti-bacterial hexachlorophene can also activate I Ks , but these compounds exert stronger potentiation on KCNQ1/KCNE1 channels than on homomeric KCNQ1 channels 96,97 . Unlike other KCNQ1 channel activators, the negative shift of voltage dependence of channel activation produced by phenylboronic acid is independent of KCNE1 subunits 98 .…”
Section: Molecular Pharmacology Of Cardiac Delayed Rectifier K+ Channelsmentioning
confidence: 99%
“…However, one Kv7.1 mutation is reported to disrupt R-L3 binding and, thereby, channel activation [20]. Recently, further Kv7.1 activators have been described [22][23][24][25]. Potent activators of Kv7.4 include BMS-204352 [26], but often lack selectivity.…”
Section: Introductionmentioning
confidence: 99%